FILOSOFI ARSITEKTUR MASJID AL-MISHBAH:Studi Arsemiotika Ikon-Indeks-Simbol - Gunardi, Yudhi; Handayani, Sri; Permana, Asep Yudi; Widaningsih, Lilis (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2021)
Abstract: Al-Mishbah Mosque is an architectural work with unique contemporary ideas and symbolic meaning requirements so that its existence is interesting to study. The researcher who is also the architect of the Al-Mishbah Mosque aims to examine the visually identified symbolic signs and describe the meaning of the architectural philosophy behind the design of the Al-Mishbah Mosque. This study uses a qualitative descriptive method and is analyzed using the theory of architectural semiotics (arsemiotics) to investigate signs which, according to Charles Sanders Peirce, are icons, indexes, and symbols. Based on the analysis of visually identified signs, the results of this study can be concluded that the signs and meanings of the architectural philosophy of the Al-Mishbah Mosque are as follows: (1) The black cube shape in the main building, is a symbolic idea of the Kaaba, which means as the center of the building. Qibla orientation of Muslim prayer, as well as a symbol of one direction and unity of Muslims. (2) The shape of the asymmetrical curved concrete hat is a symbolic idea of people prostrating, which means the main function as a mosque (a place of prostration), also has a meaning as a symbol of servitude to Allah. (3) The form of the text lafadz